Tax Avoidance, Good Corporate Governance, And Firm Risk: The Moderating Role Of Tax Risk In The Banking Sector - Alfita Maharani, Saka; Fury Puspita, Ayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study examines the role of tax avoidance and Good Corporate Governance (GCG) in shaping corporate risk in the Indonesian banking sector, where increasing regulatory scrutiny and market volatility highlight the importance of effective risk management. The study aims to analyse the effect of tax avoidance and GCG on corporate risk, with tax risk serving as a moderating variable. Using a quantitative approach, this research employs panel data regression and Moderated Regression Analysis (MRA) on 68 firm-year observations from 16 banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The findings indicate that tax avoidance has a positive effect on corporate risk, suggesting that aggressive tax strategies increase uncertainty and risk exposure. GCG, proxied by the proportion of independent commissioners, also shows a positive effect on corporate risk. Furthermore, tax risk strengthens the positive relationship between tax avoidance and corporate risk, while weakening the relationship between GCG and corporate risk. These results imply that tax-related uncertainty can undermine governance mechanisms. Practically, the findings suggest that regulators such as the Financial Services Authority (OJK) should strengthen supervision of tax-related risks, while bank management should integrate tax risk considerations into governance and risk management frameworks to enhance financial stability.